A review of the genus Polemistus de Saussure (Hymenoptera: Crabronidae) with the description of a new species from India - Rajan, Tessy; Kumar, P. Girish; Sureshan, P.m.; Hegde, V.d. (Zootaxa, 2024)
A review of the genus Polemistus de Saussure has resulted in identifying and describing a new species from Kerala viz., P. jaferi Tessy, Girish Kumar & Sureshan sp. nov. A key to species of Polemistus from the Indian subcontinent is provided.